Necessidade da conciliação de medicamentos : avaliação da história da farmacoterapia de pacientes admitidos em um hospital universitário - Silvestre, Carina Carvalho (2014)
BACKGROUND. The patient safety is a global concern. In this context, practices for the prevention and correction of drugs arise such as medication reconciliation. Thus, investigations on obtaining the history of use of pharmacotherapy on admission are required for such actions. OBJECTIVE. Investigate the history of medication use in patients admitted to a University Hospital (HU/UFS). METHODS. Step 1 corresponds to a systematic review which selected articles about medication reconciliation conducted by pharmacists at time of hospital admission. Step 2, corresponded to the assessment of discrepancies in the pharmacotherapy of patients admitted to the HU/UFS. RESULTS. The systematic review (step 1) evaluated 12 articles, which showed that medication reconciliation was a routine practice of hospital in three studies, in seven articles was informed that the pharmacist had clinical training and two studies reported having conducted a training for perform the reconciliation. About the evaluation of discrepancies (step 2), 358 patients were evaluated and 150 patients had one or more unintentional discrepancies in drug therapy during admission, 327 discrepancies were identified in total. CONCLUSION. A systematic review showed that most studies do not follow guidelines for medication reconciliation and that the discussion between pharmacists and physicians is the most widely used way to assess the clinical relevance of discrepancies. The cross-sectional article showed that discrepancies are prevalent in the hospital evaluated. Thus, actions that promote patient safety in hospital admission should be deployed.